2018
DOI: 10.21276/ijcmr.2018.5.12.18
|View full text |Cite
|
Sign up to set email alerts
|

Awareness regarding Eye Donation among Patients Attending Tertiary Care Hospital, Jammu, J&K, North India-Time to Educate People

Abstract: Introduction: It is observed that corneal blindness affects 12% of world's population which is amenable to treatment and main causes of corneal blindness are ocular trauma and corneal ulceration. The alarming figures rise every year, keeping India in the lead. The mainstay of treatment for restoring vision in such patients is corneal transplantation. In India awareness about eye donation in public is very low as per literature review. Hence creation of awareness carries paramount importance. Aim: To evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…In the present study, 72% AWWs were aware that there is no age-criteria for eye donation which was greater than the study by Manhas et al (22%) in OPD patients and it doesn't cause any disfigurement of face (70%) which was greater to that of study in paramedical workers (27%). 16,17 This shows that AWWs can be able to alter these misconceptions regarding eye donation in rural community. Our study observed that only 38.3% AWWs knew about care of eyes to be taken after death for donating eyes which changed to 95.3% after intervention.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the present study, 72% AWWs were aware that there is no age-criteria for eye donation which was greater than the study by Manhas et al (22%) in OPD patients and it doesn't cause any disfigurement of face (70%) which was greater to that of study in paramedical workers (27%). 16,17 This shows that AWWs can be able to alter these misconceptions regarding eye donation in rural community. Our study observed that only 38.3% AWWs knew about care of eyes to be taken after death for donating eyes which changed to 95.3% after intervention.…”
Section: Discussionmentioning
confidence: 98%
“…15,18 and less than the study by Manhas et al (100%) in OPD patients. 16 Donor's consent is not mandatory but the consent of family member/relatives is required after death for eye donation. The study observed that 73.26% AWWs were aware that if the person has not pledged for eyes, his relatives can donate eyes after his death was similar to the study in paramedical workers and greater than the study by Bhandary et al (55.6%), the study by Gupta et al (8.5%) and by Khan et al (56.5%).…”
Section: Discussionmentioning
confidence: 99%
“…259 transplantation. 4 As per the National Program for Control of Blindness (NPCB), prevalence of corneal blindness in India is 0.9%, 6 cases are expected to rise from 6.8 million to 10 million by 2020. 2 Due to insufficient number of eye donations in India, the gap between donor and recipient keeps on growing 30,000 cases are added every year.…”
Section: Introductionmentioning
confidence: 99%
“…2 Thus, number of patients waiting for corneal transplantation is keeps on increasing. 6 Eye donation is voluntary donation of one's eyes after his/her death. As per Eye Bank Association of India current corneal procurement rate is 49,000 per year, 2 however large number of these cornea are deemed unfit for transplantation donor corneas are unfit for corneal transplantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation